Cationic graphene oxide nanoplatform mediates miR-101 delivery to promote apoptosis by regulating autophagy and stress - Assali A (Dove Medical Press, 2018)
Akram Assali,1 Omid Akhavan,2 Fatemeh Mottaghitalab,1 Mohsen Adeli,3 Rassoul Dinarvand,1 Shayan Razzazan,4 Ehsan Arefian,5 Masoud Soleimani,6 Fatemeh Atyabi1 1Nanotechnology Research Center, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Physics, Sharif University of Technology, Tehran, Iran; 3Department of Biology, Chemistry, Pharmacy, Institute of Chemistry and Biochemistry, Freie University Berlin, Berlin, Germany; 4Department of Electrical Engineering, Amirkabir University of Technology, Tehran, Iran; 5Molecular Virology Lab, Department of Microbiology, School of Biology, College of Science, University of Tehran, Tehran, Iran; 6Hematology Department, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran Introduction: MicroRNA-101 (miR-101) is an intense cancer suppressor with special algorithm to target a wide range of pathways and genes which indicates the ability to regulate apoptosis, cellular stress, metastasis, autophagy, and tumor growth. Silencing of some genes such as Stathmin1 with miR-101 can be interpreted as apoptotic accelerator and autophagy suppressor. It is hypothesized that hybrid microRNA (miRNA) delivery structures based on cationized graphene oxide (GO) could take superiority of targeting and photothermal therapy to suppress the cancer cells.Materials and methods: In this study, GO nanoplatforms were covalently decorated with polyethylene glycol (PEG) and poly-L-arginine (P-L-Arg) that reduced the surface of GO and increased the near infrared absorption ~7.5-fold higher than nonreduced GO.Results: The prepared nanoplatform [GO-PEG-(P-L-Arg)] showed higher miRNA payload and greater internalization and facilitated endosomal scape into the cytoplasm in comparison with GO-PEG. Furthermore, applying P-L-Arg, as a targeting agent, greatly improved the selective transfection of nanoplatform in cancer cells (MCF7, MDA-MB-231) in comparison with immortalized breast cells and fibroblast primary cells. Treating cancer cells with GO-PEG-(P-L-Arg)/miR-101 and incorporating near infrared laser irradiation induced 68% apoptosis and suppressed Stathmin1 protein.Conclusion: The obtained results indicated that GO-PEG-(P-L-Arg) would be a suitable targeted delivery system of miR-101 transfection that could downregulate autophagy and conduct thermal stress to activate apoptotic cascades when combined with photothermal therapy. Keywords: miR-101, cationized graphene oxide, poly-L-arginine, apoptosis, autophagy, photothermal therapy